Design steps and performance of aerated lagoon, oxidation ditch and wetland methods for Erbil municipal wastewater treatment and reusing - Qarani Aziz Shuokr; Adnan Kurdistan Neyaz; Mojiri Amin; Bashir Mohammed J.K. (Reciklaža i Održivi Razvoj, 2023)
The objectives of the current study were to investigate the characterization, treatment techniques and reuse of fresh municipal wastewater (MWW) from the east-south area of Erbil city, Kurdistan Region, Iraq. The collected wastewater samples were analyzed for 21 quality parameters. Some of the quality parameters such as color (146 Pt. Co and 337 Pt. Co), total solids (800 mg/L), suspended solids (400 mg/L and 1100 mg/L), nitrate (17.7 mg/L), nitrite (11 mg/L and 29 mg/L), and ammonia (2.09 mg/L and 2.64 mg/L) exceeded the standards for wastewater disposal. Accordingly, treatment was required before the wastewater could be discharged to the natural environment. Treatment techniques such as aerated lagoons, oxidation ditches, and wetlands were designed and investigated. Design procedures, calculations, and performance for each treatment method were explained. The total area designed for aerated lagoons, oxidation ditches, and wetlands was 72000 m2, 17180 m2, and 25200 m2, respectively. In general, the wetland method was the most effective method with efficiencies of 91.6 % for biochemical oxygen demand, 90.4 % for chemical oxygen demand, 85.7 % for ammonia, and 91.8 % for suspended solids. Treated wastewater can be reused for irrigation purposes and is completely safe for irrigation. The use of treated wastewater from the east-south part of the city of Erbil for irrigation instead of drinking water is economical and leads to the conservation of drinking water sources.